Duration of rhegmatogenous retinal detachment predicts recovery of retinal sensitivity - Rose, Rose (Universa Medicina, 2009)
The decision to treat a disease is often based on the presence or absence of symptoms, one prototype case being rhegmatogenous retinal detachment. Detachment of the neural retina from the pigment epithelium is a major cause of anatomical and functional dysfunction of the retina, where retinal recovery is inversely related to duration of detachment. The purpose of retinal reattachment is to effect recovery of the photoreceptors and pigment epithelium from degeneration. The aim of this study was to determine the critical duration of rhegmatogenous retinal detachment resulting in optimal retinal recovery after reattachment. A prospective study was conducted at a private hospital in Yogyakarta. Thirty five eyes were involved in this study. Three months after reattachment, central retinal recovery was measured by means of a Goldmann manual kinetic perimeter. The results showed that retinal recovery developed three months after surgery if the onset of rhegmatogenous retinal detachment was less than 28 days before surgery. The results were not significant if the onset of rhegmatogenous retinal detachment was more than 35 days. Although the Goldmann manual kinetic perimeter can efficiently detect central retinal sensitivity, it should be supported by more sensitive tools to evaluate the anatomy and function of the retina.